Pandemonium and parade : Japanese monsters and the culture of yōkai - Foster, Michael Dylan, 1965- (University of California Press, 2009)
Monsters known as yōkai have long haunted the Japanese cultural landscape. This history of the strange and mysterious in Japan seeks out these creatures in folklore, encyclopedias, literature, art, science, games, manga, magazines and movies, exploring their meanings in the Japanese imagination over three centuries.